Gender Roles and Socially Constructed Relations in the Bugis–Makassar Cultural Context: A Study of Krishna Pabichara’s Natisha and Lakuna - Ahmad, Nur Aina; Fatsah, Hasanuddin; Masie, Sitti Rachmi; Salam, Salam (International Journal of Language and Literary Studies, 2026)
Literary works function as cultural texts that reflect and negotiate social values, including gender constructions within specific communities. This study examines the gender roles and relations of the Bugis–Makassar community as represented in Natisha and Lakuna by Krishna Pabichara, focusing on socio-cultural values transmitted across generations as normative frameworks shaping gender identities. The research employs a qualitative descriptive approach. Data were collected by categorizing narrative passages and character dialogues that depict male and female roles within the Bugis–Makassar cultural context. The findings reveal that gender roles and relations in both novels are grounded in the socio-cultural value of siri’ (self-respect and honor). Traditionally, men are positioned as protectors and breadwinners, while women serve as guardians of family honor and managers of the domestic sphere. Women are regarded as the core embodiment of siri’, yet they also hold a central role within the household. The evolving interpretation of siri’ promotes greater gender balance, encouraging women to pursue education and independence to uphold family dignity.